Landscape-scale conservation design across biotic realms: sequential integration of aquatic and terrestrial landscapes. Issue 1 (December 2017) - Leonard, Paul; Baldwin, Robert; Hanks, R.
Abstract Systematic conservation planning has been used extensively throughout the world to identify important areas for maintaining biodiversity and functional ecosystems, and is well suited to address large-scale biodiversity conservation challenges of the twenty-first century. Systematic planning is necessary to bridge implementation, scale, and data gaps in a collaborative effort that recognizes competing land uses. Here, we developed a conservation planning process to identify and unify conservation priorities around the central and southern Appalachian Mountains as part of the Appalachian Landscape Conservation Cooperative (App LCC). Through a participatory framework and sequential, cross-realm integration in spatial optimization modeling we highlight lands and waters that together achieve joint conservation goals from LCC partners for the least cost. This process was driven by a synthesis of 26 multi-scaled conservation targets and optimized for simultaneous representation inside the program Marxan to account for roughly 25% of the LCC geography. We identify five conservation design elements covering critical ecological processes and patterns including interconnected regions as well as the broad landscapes between them. Elements were then subjected to a cumulative threats index for possible prioritization. The evaluation of these elements supports multi-scaled decision making within the LCC planning community through a participatory, dynamic, and iterative process.